THE INFLUENCE OF TOXIC ELEMENTS ON ORGANOLEPTIC MILK INDICATORS - Shcherbakova, N. S.; Maksymova, Yu. Yu. (Scientific Progress & Innovations, 2019)
Heavy metals, which are toxic to humans and animals, are one of the most dangerous forms of food and the environment contamination. These substances penetrate into the human body mainly through food. For this reason, it is important to identify sources of accumulation and pollution and trace the pathways of these metals to farm products. The prevention of heavy metals’ hazardous impact on human health has to be based on measures covering the entire migration link, from reducing metal accumulation in the natural environ-ment to controlling their content in food. Farm animals are the leading link in the soil-plant-animal-food system, as they receive various organic substances and chemical elements, including heavy metals with feed and water. Milk is the most “susceptible” to heavy metals. The most toxic elements are lead, mercury, cad-mium, zinc and arsenic. The research was conducted in 2019 at the Regional State Laboratory of the State Food Consumer Service in Poltava region. Altogether 12 samples of cow's whole milk were examined− one sample per batch. While examining the attention was paid to organoleptic indicators: color, taste, smell, and consistency. At conducting chemical-analytical studies of milk the mass concentration of micro- and macro-elements was determined using appropriate test procedures and modern devices. As a result, it was found that the content of mercury (Hd) in the tested samples was in accordance with the standard. The content of cadmium (Cd) in sample № 2 was 0.056 mg/kg, in sample № 3 – 0.042 mg/kg, in sample № 9 – 0.047, and in sample № 10 – 0.059 at the maximum permissible level of 0.03 mg/kg, which was 86.6 %, 40 %, 56 % and 96 % respectively higher than the standard. Zinc (Zn) values in the test samples were within the standard range. Lead content (Pb) in sample № 2 was 0.233 mg/kg, which was 133 % higher than the standard. Lead content (Pb) in sample № 3 was 0.285 mg/kg, which was 185 % higher than the maximum permissible levels. In sample № 9, lead content was 0.249 and in sample № 10 it was 0.265, which was 149 % and 165 % re-spectively higher than the standard. The concentration of arsenic (As) in the test samples was within the normal range. In terms of organoleptic characteristics, all the tested samples met the state requirements of DSTU 3662:2018 “Raw cow milk. Specifications”.